Engineering Sketching, Journaling and IT: Synergized Learning Tools - Rahnamayiezekavat, Payam; Siew, R.; Bernold, L. (2013)
A key challenge of engineering education is to teach multifaceted content while actively engaging students with different learning preferences. The authors present an approach to synergize journaling, engineering sketching and in-class quizzing as tools to foster active learning, deeper understanding and the development of critical engineering skills including professional communication. A model will be presented that is built on the constructivist theory of learning integrated with Bloom’s taxonomy of understanding and Kolb’s model of learning preferences. The paper explains how E-learning tools were used to interact effectively with 350 students of a second year course called Engineering Construction. Examples are self-grading web-based assignments and PollEverywhere, a real-time quizzing system used in class to encourage participative learning. These tools were synergized with reflective journal writing and engineering sketching to foster understanding. In this course, students were required to pen down their weekly learning in a journal, answering questions “WHY” and “HOW” while three compulsory sketches with increasing levels of difficulty also given as assignments. The sketching of construction equipment was followed by that of accidents and crane lift plans. This forced students to apply engineering formula/guidelines from the textbook which called for higher level of understanding to analyzing. The students’ unique learning preferences (according to Kolb’s four learning styles; Why; How; What; What-if), the challenges of expressing their understanding and how they correlate with engineering sketching and journaling is discussed.